2021
DOI: 10.1097/mcg.0000000000001507
|View full text |Cite
|
Sign up to set email alerts
|

Intracystic Glucose Levels in Differentiating Mucinous From Nonmucinous Pancreatic Cysts

Abstract: Background: Mucinous pancreatic cysts are well reported to transform into pancreatic adenocarcinoma, whereas nonmucinous cysts are mostly benign with low risk for malignant transformation. Nonsurgical methods of differentiating mucinous and nonmucinous pancreatic cysts are challenging and entail a multi investigational approach. Low intracystic glucose levels have been evaluated in multiple studies for its accuracy in differentiating mucinous from nonmucinous cysts of the pancreas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The current study assesses the accuracy of PCF glucose levels for mucinous cyst diagnosis using laboratory as well as on-site glucometry measurement. Consistent with previous studies, including the original study by Park et al 8 and the recent meta-analysis by Mohan et al 15 that demonstrated a pooled sensitivity of 90.5% and a pooled specificity of 88%, our results demonstrated similar findings as low intracystic glucose (using the cutoff of 60 mg/dL) had a sensitivity of 80-87.7% and specificity of 84.6-90% in diagnosing mucinous cysts. Furthermore, although previous studies used glucose cutoff level between 50-73 mg/dL, our statistical analysis using the CART method demonstrated an improved diagnostic ability with higher glucose cutoff level of 87 mg/dL, and according to a recent meta-analysis, the mean intra-cystic glucose for mucinous lesions was 15.92 ± 6.20 and for nonmucinous lesions is 94.03 ± 12.23.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study assesses the accuracy of PCF glucose levels for mucinous cyst diagnosis using laboratory as well as on-site glucometry measurement. Consistent with previous studies, including the original study by Park et al 8 and the recent meta-analysis by Mohan et al 15 that demonstrated a pooled sensitivity of 90.5% and a pooled specificity of 88%, our results demonstrated similar findings as low intracystic glucose (using the cutoff of 60 mg/dL) had a sensitivity of 80-87.7% and specificity of 84.6-90% in diagnosing mucinous cysts. Furthermore, although previous studies used glucose cutoff level between 50-73 mg/dL, our statistical analysis using the CART method demonstrated an improved diagnostic ability with higher glucose cutoff level of 87 mg/dL, and according to a recent meta-analysis, the mean intra-cystic glucose for mucinous lesions was 15.92 ± 6.20 and for nonmucinous lesions is 94.03 ± 12.23.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of mucinous cysts in our study cohort is relatively higher than previous studies with 76% mucinous cysts, while the average prevalence according to a recent meta-analysis is about 60%. 15 The lower prevalence of non-mucinous cysts in our study cohort is most likely the result of a low neoplastic potential of the non-mucinous cysts according to clinical, radiological, and sonographic features, which usually do not require further analysis by EUS-FNA. The following characteristic can on one hand suggest more realistic glucose range and cutoff level for mucinous cysts, and on the other hand might suggest misclassification of mucinous cysts.…”
Section: Discussionmentioning
confidence: 70%
“… 15 17 A meta-analysis published in 2022 suggested that low glucose levels in cystic fluid (cut-off point: 50 mg/dL) could be used to differentiate mucinous from non-mucinous cysts of the pancreas (sensitivity: 90.8%, specificity: 90.5%). 18 For SCA/MSC, a study from 2020 reported that α-inhibin-positive cuboidal cells from aspirated cystic fluid could be helpful for diagnosing SCA. 19 However, these conclusions need to be verified by more large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 7 studies encompassing 566 patients reported that lower (cut-off < 50 mg/dL) intra-cystic glucose concentration had a pooled sensitivity of 90.1% (95%CI: 87.2-92.5) and pooled specificity of 85.3% (95%CI: 76.8-91.1) when differentiating mucinous from non-mucinous cysts[ 35 ]. In a subset analysis, point-of-care glucometer measurements for intra-cystic glucose (3 studies) also revealed comparable pooled sensitivity of 89.5% (95%CI: 85.5-92.5; I 2 = 0) and pooled specificity of 83.9% (95%CI: 68.5-92.6; I 2 = 43) for the differentiation of PCLs[ 35 ].…”
Section: Traditional Diagnostic Approaches Using Biomarkersmentioning
confidence: 99%
“…A meta-analysis of 7 studies encompassing 566 patients reported that lower (cut-off < 50 mg/dL) intra-cystic glucose concentration had a pooled sensitivity of 90.1% (95%CI: 87.2-92.5) and pooled specificity of 85.3% (95%CI: 76.8-91.1) when differentiating mucinous from non-mucinous cysts[ 35 ]. In a subset analysis, point-of-care glucometer measurements for intra-cystic glucose (3 studies) also revealed comparable pooled sensitivity of 89.5% (95%CI: 85.5-92.5; I 2 = 0) and pooled specificity of 83.9% (95%CI: 68.5-92.6; I 2 = 43) for the differentiation of PCLs[ 35 ]. A more recent (2021) meta-analysis that included 8 studies with 609 PCLs showed pooled sensitivities for glucose vs CEA of 91% (95%CI: 88-94) vs 56% (95%CI 46-66) (comparative P value < 0.001), pooled specificities were 86% (95%CI: 81-90) vs 96% (95%CI: 90-99), P > 0.05, respectively[ 36 ].…”
Section: Traditional Diagnostic Approaches Using Biomarkersmentioning
confidence: 99%